Pembuatan kulit imitasi untuk atasan sepatu dengan variasi jumlah blowing agent ADCM - Soepranoto, Soepranoto (Majalah Kulit, Karet, dan Plastik, 1989)
Experiments of making PVC synthetic leather for shoe upper has been done by varying ADCM blowing agent and the temperature of the middle coat layer coating process.The composition used for each layer of the synthetic leather are :Top coat (part)Â Â Â Â Â Â Â Â Â Â Â  : PVC emulsion 100, DOP 70, Epoxy oil 3, VM 1700/5 stabilizer 5, CaCO3 filler 10, Stearic acid 1, Pigment 1.Middle coat (part)Â Â Â Â Â Â  : PVC emulsion 100, DOP 50, Epoxy oil 3, VM 1700/5 Stabilizer 5, CaCO3 filler 10, ADCM blowing agent 2 â 6, Activator (KK 42) 3, VS â 103 1.Base coat (part)Â Â Â Â Â Â Â Â Â  : PVC emulsion 100, Epoxy oil 3, VM 1700/5 Stabilizer 5.TemperatureÂ Â Â Â Â Â Â Â Â Â Â Â Â Â  : 150 â 1700 CVariationThe supporting material used in this coating process is flannel fabric. The productâre 25 kinds of synthetic leather with Â± 1 mm thickness and had been tested for physical properties such as : tensile strength, elongation at break, tear strength, adhesion strength between plastic layer and supporting textile fabric, flexing and stitch tear strength.The optimum value of physical properties were achieved by the synthetic leather in which contain 6 parts of ADCM blowing agent, processed at 1650 C. it couldÂ  be graded into the specification of Indonesian Industri al Standard number SII 1645 â 85 : Synthetic leather for shoe uppers.